The dual role of autophagy in periprosthetic osteolysis - Yin, Zhaoyang; Gong, Ge; Wang, Xiang; Liu, Wei; Wang, Bin; Yin, Jian (Frontiers in Cell and Developmental Biology, 2023)
Periprosthetic osteolysis (PPO) induced by wear particles is an important cause of aseptic loosening after artificial joint replacement, among which the imbalance of osteogenesis and osteoclastic processes occupies a central position. The cells involved in PPO mainly include osteoclasts (macrophages), osteoblasts, osteocytes, and fibroblasts. RANKL/RANK/OGP axis is a typical way for osteolysis. Autophagy, a mode of regulatory cell death and maintenance of cellular homeostasis, has a dual role in PPO. Although autophagy is activated in various periprosthetic cells and regulates the release of inflammatory cytokines, osteoclast activation, and osteoblast differentiation, its beneficial or detrimental role remains a mystery. This article focuses on the role of autophagy in PPO, and expects the regulation of autophagy to become a powerful target for clinical treatment of PPO.